2002
DOI: 10.1039/b203198c
|View full text |Cite
|
Sign up to set email alerts
|

Al(iii)-binding properties of iminodiacetic acid, nitrilotriacetic acid and their mixed carboxylic–phosphonic derivatives

Abstract: Potentiometric, 1 H, 31 P NMR spectroscopic and X-ray studies were carried out to investigate the complex formation of Al() with iminodiacetic acid (IDA), nitrilotriacetic acid (NTA), their mixed carboxylic-phosphonic and purely phosphonic derivatives. The stability constants of the complexes formed were determined at 25 ЊC and at 0.2 mol dm Ϫ3 ionic strength (KCl). It was found that substitution of CO 2 Ϫ by PO 3 2Ϫ increases the overall stability of the complexes, due to the higher basicity of the phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…In the next two deprotonation steps, (a) the metal ion-induced deprotonation and the subsequent coordination of the alcoholic-OH, and (b) the ionization of a coordinated water molecule, take place in parallel overlapping processes, with stepwise pK values of 4.24 and 5.13. The deprotonation processes might be accompanied by a structural rearrangement from octahedral to tetrahedral geometry, which is rather frequent in the case of ternary hydroxo complexes of Al(III) [33,54]. In the presence of excess ligand, Al(III)-HEDP 1:2 bis-complexes may also form, in which a second ligand molecule coordinates to the 1:1 mono-complexes with a different protonation/deprotonation state.…”
Section: Speciation Studies Of the Binary Al(iii)-hedp Systemmentioning
confidence: 96%
See 2 more Smart Citations
“…In the next two deprotonation steps, (a) the metal ion-induced deprotonation and the subsequent coordination of the alcoholic-OH, and (b) the ionization of a coordinated water molecule, take place in parallel overlapping processes, with stepwise pK values of 4.24 and 5.13. The deprotonation processes might be accompanied by a structural rearrangement from octahedral to tetrahedral geometry, which is rather frequent in the case of ternary hydroxo complexes of Al(III) [33,54]. In the presence of excess ligand, Al(III)-HEDP 1:2 bis-complexes may also form, in which a second ligand molecule coordinates to the 1:1 mono-complexes with a different protonation/deprotonation state.…”
Section: Speciation Studies Of the Binary Al(iii)-hedp Systemmentioning
confidence: 96%
“…In solution, 31 P NMR for 1 upon dissolution and at the equilibrium state suggests that the species does not retain its solid-state structure in solution. The aqueous speciation studies [33], in the examined pH range, revealed the presence of two species. These are [AlA] and [AlAH À1 ].…”
Section: Correlation Of the Aqueous Binary Al(iii)-phosphonate Speciamentioning
confidence: 98%
See 1 more Smart Citation
“…In the case of a rigid dimer, at least three different P resonances should occur in the spectra: (i) the P atoms of the two CH 2 PO 3 2Ϫ arms at the coordinating side of the molecule, (ii) the coordinated P of the partially bound side of the molecule, and (iii) the P of the non-coordinating CH 2 PO 3 2Ϫ arm of this side. On the other hand, in the case of a flexible dimer the methylene protons in the N-attached phosphonate arms should become equivalent resulting in the appearance of a high-intensity doublet in the 1 H NMR spectra, which is not observed, instead rather complicated spectra are obtained (see Figure 4) were suggested by Westerback et al [7] and by Motekaitis et al, [10] and partly confirmed by Jarvis et al [11] [22,24] The pK a calculated from the data in Table 3 for the deprotonation of [AlLH] 4Ϫ to produce [AlL] 5Ϫ is 6.26, significantly lower than the pK a of the free ligand with the same number of protons, HL (pK a ഠ 13; see Table 2). This considerable decrease in the pK a of the HL 7Ϫ proton due to the coordination of Al III indicates the high stability of the hexadentate coordinated complex [AlL] 5Ϫ .…”
Section: Complexesmentioning
confidence: 63%
“…A similar hexadentate coordination mode was assumed for the carboxylate analogue EDTA in its [AlL] Ϫ complex. [22,24] This structure is rather rigid, accounting for the narrow peaks in the NMR spectra obtained, and has a C 2 symmetry axis so that the phosphorus atoms and the protons are equivalent in a pairwise manner. The CH 2 PO 3 2Ϫ arms bound to the same N atom are not equivalent; for this reason two 31 P signals of equal intensity are observed.…”
Section: Complexesmentioning
confidence: 99%